1981
DOI: 10.1007/bf00429209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lithium carbonate on methylphenidate-induced mood, behavior, and cognitive processes

Abstract: Evidence is presented which suggests that lithium modifies the mood and behavioral alterations resulting from IV methylphenidate. Specifically, lithium significantly reduces the level of arousal-activation, euphoria-grandiosity, and the total score of manic-state ratings following a methylphenidate challenge. In addition, lithium appears to be capable of modifying the growth hormone response to methylphenidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In a double-blind study of depressed patients, the euphoriant and/or activating effects of amphetamine were also either attenuated or blocked by lithium (Van Kammen and Murphy, 1975). Other double-blind studies have shown the same effect of lithium on schizophrenic patients treated with amphetamine (Van Kammen et al, 1985), as well as on patients with a variety of other psychiatric illnesses (Huey et al, 1981).…”
Section: Lithium and Stimulants In Humansmentioning
confidence: 89%
“…In a double-blind study of depressed patients, the euphoriant and/or activating effects of amphetamine were also either attenuated or blocked by lithium (Van Kammen and Murphy, 1975). Other double-blind studies have shown the same effect of lithium on schizophrenic patients treated with amphetamine (Van Kammen et al, 1985), as well as on patients with a variety of other psychiatric illnesses (Huey et al, 1981).…”
Section: Lithium and Stimulants In Humansmentioning
confidence: 89%
“…The hyperactivity is attenuated by antipsychotic drugs as well as anticonvulsants often utilized for the treatment of bipolar disorder (Lamberty et al, 2001). It also has validity in the sense that amphetamine commonly precipitates manic episodes in susceptible individual who suffer from bipolar disorderFan effect that may be attenuated by lithium (Huey et al, 1981;van Kammen et al, 1985;Van Kammen and Murphy, 1975). Further, the motoric changes in activity present in bipolar disorder are among the most defining characteristics of the illness, ranging from near catatonic immobility to the profound hyperactivity of manic states.…”
Section: Recent Support From Animal Behavioral Models and Genetic Stumentioning
confidence: 99%
“…The use of dopaminergic stimulants has been associated with the onset of mania in bipolar patients and with manic-like symptoms in control subjects (Anand et al, 2000;Mamelak, 1978;Murphy et al, 1971;Peet and Peters, 1995). Some studies report that lithium can attenuate or prevent the behavioral and/or functional effects of dopaminergic drugs Huey et al, 1981;Silverstone et al, 1998;van Kammen et al, 1985;Van Kammen and Murphy, 1975;Willson et al, 2005). These data have led to the suggestion that how the human brain responds to dopaminergic stimulants may be a clinical endophenotype of bipolar disorder (Hasler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%